2020
DOI: 10.3390/clockssleep2030027
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Oximetry for Diagnosing Obstructive Sleep Apnea in a Clinical Setting

Abstract: A large epidemiological study using oximetry to analyze obstructive sleep apnea (OSA) and metabolic comorbidities was performed in Japan; however, reliability and validity of oximetry in the Japanese population remains poorly understood. In this study, oximetry data from the epidemiological study were compared with data from clinically performed polysomnography (PSG) and out-of-center sleep testing (OCST) in epidemiological study participants who later attended our outpatient units. The oxygen desaturation ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…We used the same in-laboratory PSG device; however, the OCST devices were different between the two settings. A comparison between AHI from PSG and REI from OCST was previously performed in the city hospital, which suggested a reasonable validity of REI compared with AHI [24]. The same sleep physician reviewed all of the analysed results; however, the PSG/OCST analyses were performed by different staff in both settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the same in-laboratory PSG device; however, the OCST devices were different between the two settings. A comparison between AHI from PSG and REI from OCST was previously performed in the city hospital, which suggested a reasonable validity of REI compared with AHI [24]. The same sleep physician reviewed all of the analysed results; however, the PSG/OCST analyses were performed by different staff in both settings.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical tools, questionnaires, and prediction algorithms are strongly not recommended to diagnose OSA in the absence of polysomnography (PSG) or out-of-centre sleep testing (OCST) [23]. Pulse oximetry, a simple method to obtain physiological signals, may be another useful tool for screening OSA; however, it may be difficult to set an appropriate threshold to distinguish between moderate and severe OSA by oximetry alone [24].…”
Section: Introductionmentioning
confidence: 99%
“…The variables associated with the severity of OSA ( 19), such as BMI, age, sex, and positional component, are commonly mentioned in the studies, yet they are not parameterized (16)(17)(18). Fabius et al (24) mentioned age and BMI as covariables that influence the relationship between AHI and ODI, owing to greater desaturation in the elderly.…”
Section: ' Discussionmentioning
confidence: 99%
“…Thus, it is necessary to investigate simpler and less expensive methods to expand access to OSA diagnosis. Previous studies (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) have assessed the ability of pulse oximetry to diagnose OSA; they observed that compared to the apnea-hypopnea index (AHI), the oxyhemoglobin desaturation index (ODI)-measured using the oximeterexhibited high sensitivity and specificity for diagnosing OSA. However, in most studies, validation was performed based on comparison of the test results in a controlled environmente.g., PSG type I in the laboratory-with different sampling designs, thus questions are raised regarding the diagnostic viability of ODI values measured in a laboratory environment for extrapolation in an unsupervised home environment.…”
Section: ' Introductionmentioning
confidence: 99%
“…AIS score and sleep duration in this population were 6.82 ± 3.69 and 5.96 ± 1.13 h, respectively ( Table 1 ). AIS scores among city government employees and patients in a sleep apnoea outpatient unit in Japan were 4.98 ± 3.57 [ 4 ] and 3.64 ± 3.15 [ 24 ], respectively. Sleep duration in Japanese general population was reported to be 7.25–7.37 h [ 8 , 12 ].…”
Section: Discussionmentioning
confidence: 99%